Embodied carbon assessment using a dynamic climate model: Case-study comparison of a concrete, steel and timber building structure. (October 2021) - Hawkins, Will; Cooper, Samuel; Allen, Stephen; Roynon, Jonathan; Ibell, Tim
Abstract: The enormous environmental impact of construction is becoming increasingly apparent and unacceptable to many structural engineers, whose designs typically account for the majority of a building's embodied carbon. It is timely, therefore, that consensus is forming around a methodology for calculating embodied carbon. This encourages the inclusion of all life cycle stages, from material production and construction, through use and eventual demolition, disposal and reuse. In practice, however, end-of-life processes are fraught with uncertainty and often ignored, despite the potentially large associated carbon fluxes. Further uncertainty exists when considering bio-based construction materials, which store carbon during use. There are no widely-accepted means of accounting for timing of these carbon fluxes, despite the long service life of most buildings. Could we consider whole-life carbon in a more holistic and climate-focused way? This article uses dynamic life cycle assessment to convert greenhouse gas emission histories to key climate impacts using a simple dynamic model. The implications for structural design decisions are explored by comparing concrete, steel and timber options for a typical medium-rise building structure. Concrete is found to have a higher impact than steel, with the climate response of both options dominated by the large initial emissions of material production and construction. Timber has the smallest impact, for this example, under a typical scenario with sustainable forest management and re-emission of sequestered carbon at end-of-life. The analysis takes a forward-looking approach to sequestration, with timing corresponding to the growth of replanted trees. An optimistic timber scenario, whereby future carbon-capture technology avoids most end-of-life emissions, demonstrates the possibility of structures with small long-term climate cooling effects. Conversely, in a hypothetical worst-case scenario where no replanting or subsequent sequestration occurs, the long-term warming effect of the timber structure is increased by the net emission of biogenic carbon. Although end-of-life processes are important in the long-term, particularly for timber, the analysis also highlights the importance of the initial emissions from material production and construction. These cause high rates of short-term temperature increase and prolonged accumulation of radiative heat for all the buildings, but the impacts are again lowest for timber. Most importantly, the investigation shows how dynamic life cycle assessment can be used to explore climate impacts in a comprehensive, graphical and unbiased way. As a simple extension to established methodologies for calculating embodied carbon, it is a powerful decision making tool in the climate emergency.